If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + n = 6n + 22 Reorder the terms: -3 + n = 22 + 6n Solving -3 + n = 22 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. -3 + n + -6n = 22 + 6n + -6n Combine like terms: n + -6n = -5n -3 + -5n = 22 + 6n + -6n Combine like terms: 6n + -6n = 0 -3 + -5n = 22 + 0 -3 + -5n = 22 Add '3' to each side of the equation. -3 + 3 + -5n = 22 + 3 Combine like terms: -3 + 3 = 0 0 + -5n = 22 + 3 -5n = 22 + 3 Combine like terms: 22 + 3 = 25 -5n = 25 Divide each side by '-5'. n = -5 Simplifying n = -5
| 3(x-2)=5x+4 | | 1/3x+15=20 | | 4x-2+5x+10+2x+14=0 | | 2x+3=60 | | 2x+5=3x+20 | | -x+11/12=-5/12 | | 1/3(6-15w)=3/8(40w-8) | | -x/2=-6 | | 12y=5y+42 | | 1/2y=1/3y+2 | | 14x+4=9x+7 | | 9y=4y+120 | | 2w^2=-11w-5 | | 6=-2(x+8)-5x | | 4y-(8+2.3y)-x=5+2y | | 9x=-80 | | 220=2(2w-40)+2(w+1) | | -3d-5=28 | | 3513x-4= | | W/4+15=28 | | x^2=3x^2+29 | | 7(1-7x)=-3x-39 | | 3.3-3=15-1.2h | | Y/8+5=-3 | | 45=5x+7(2x-18) | | 45=2x+5 | | 88=4x+4(3x-18) | | -8-8(6n+1)=n | | 8x+11=99 | | w+2/5=7/5 | | 6/5/18/7 | | 2^2x^8/2^5x^6 |